Impact of Presurgical Breast Magnetic Resonance Imaging (MRI) on Surgical Planning – A Retrospective Analysis from a Private Radiology Group. Issue 2 (7th January 2013) - Fan, X. Cynthia; Nemoto, Takuma; Blatto, Karen; Mangiafesto, Emily; Sundberg, Jodi; Chen, Anna; Foti, Anthony; Holzhauer, Markus; Lahr, Patrick; Snitzer, Eric; Summers, Thomas; Wolf, David; et al.
Abstract Presurgical bilateral breast MRI is being increasingly utilized in newly diagnosed breast cancer patients to identify the presence of other potentially malignant lesions and thereby guide surgical planning. The authors have performed a retrospective analysis of presurgical MRIs in 445 breast cancer patients, consecutively seen in a community practice setting, to determine what risk factors may be associated with bilateral synchronous breast cancer. Clinical, imaging, surgical, and pathological data were collected on these newly diagnosed patients, who underwent presurgical breast MRIs from November 1, 2008 through October 31, 2009. The MRIs detected 84 incremental (additional) malignancies in 66 (14.8%) patients, including 22 patients in the contralateral breast (4.9%) and 48 patients who had ipsilateral incremental malignancies (10.8%). The presurgical breast MRIs had a sensitivity of 99% and a specificity of 86%. Based on the imaging study and the subsequent biopsy(s), 105 patients (23.6%) had changes in their surgical planning. For those with incremental breast malignancies, the synchronous bilateral breast cancer patients were older (67.5 ± 13.5 years, p = 0.01). Patients with ipsilateral incremental malignancies were younger (55.6 ± 10.4 years of age, p = 0.03). A strong family history and ductal carcinoma in situ (DCIS) as the index lesion also appeared to be associated with increased bilateral malignancy detection. The authors conclude that although presurgical MRI remains controversial, our data support its role in surgical planning for newly diagnosed breast cancer patients.